Les lois sociales et les indemnités qui en découlent - SSQ, Mutuelle (Assurances)

(untitled) (HEC Montréal, 1983)
With the consent of S.S.Q. Mutual Group Insurance Company, we present to you the text of the excellent newsletter which the company dedicates each year to the various federal and provincial social legislations to which the taxpayer may resort to. Following is the introduction to this study: a) Contained in the S.S.Q. Newsletter are various particulars with respect to the provisions of social legislations from both the Federal and Provincial levels of government. Unless indicated otherwise, the information, obtained from reliable sources, reflects the situation as at January 1st 1983. b) Changes having occurred since January 1982 include an increase in the cost of hospital rooms, a major amendment respecting the reimbursement of hospitalization expenses outside of Canada, amendments to the Québec Automobile Insurance Act and more detailed particulars respecting the Labour Standards Act (Québec).